To convert the given quadratic from vertex form \( y = 2(x - 5)^2 - 10 \) to standard form \( y = ax^2 + bx + c \), we need to expand the expression.
-
Start by expanding the squared term: \[ (x - 5)^2 = x^2 - 10x + 25 \]
-
Substitute this back into the equation: \[ y = 2(x^2 - 10x + 25) - 10 \]
-
Distribute the 2: \[ y = 2x^2 - 20x + 50 - 10 \]
-
Combine the constant terms: \[ y = 2x^2 - 20x + 40 \]
Thus, the standard form of the quadratic is: \[ y = 2x^2 - 20x + 40 \]
In this case, \( a = 2 \), \( b = -20 \), and \( c = 40 \).
So the final answer is: \[ y = x^2 + (-20)x + 40 \]